A-SLOTH: ancient stars and local observables by tracing Hhalos - Magg, Mattis; Hartwig, Tilman; Chen, Li-Hsin; Tarumi, Yuta (The journal of open source software, 2022)
Magg et al., (2022). A-SLOTH: Ancient Stars and Local Observables by Tracing Halos. Journal of Open Source Software, 7(74), 4417, https://doi.org/10.21105/joss.04417
Gesehen am 18.10.2022